The Antifungal Effects of Equol Against Candida albicans Involve Mitochondrial Dysfunction - Anni Ge; Hao Zhou; Xi Yang; Chunling Zhao; Caiyan Xin; Zhangyong Song (Journal of Fungi)
Novel antifungal agents are urgently needed because of the increasing number of drug-resistant Candida strains encountered in clinical practice and the limited variety of available antifungal drugs. Equol, a metabolite of soy isoflavone glycosides, exhibits antifungal activities. In this study, Equol had good inhibitory activity against Candida species. The lowest inhibitory concentration of 125–500 μg/mL was confirmed by the gradient dilution method. In addition, transmission electron microscopy and the relative content assay showed that Equol altered the cell wall and membrane of Candida albicans. Further studies found that Equol treatment increased the intracellular levels of reactive oxygen species and Ca2+. Subsequent experiments suggested that Equol treatment depolarized the membrane potential of C. albicans and up-regulated the expression of the apoptosis-inducing factor gene. These results confirmed that Equol damaged the cell wall and membrane, dysregulated the intracellular components, induced oxidative stress and Ca2+ accumulation, and ultimately resulted in mitochondrial dysfunction. Collectively, these findings demonstrated that Equol is a potential antifungal agent.